Sex-Specific Automatic Responses to Infant Cries: TMS Reveals Greater Excitability in Females than Males in Motor Evoked Potentials - Messina, Irene; Cattaneo, Luigi; Venuti, Paola; de Pisapia, Nicola; Serra, Mauro; Esposito, Gianluca; Rigo, Paola; Farneti, Alessandra; Bornstein, Marc H. (Frontiers in Psychology, 2016)
Neuroimaging reveals that infant cries activate parts of the premotor cortical system. To validate this effect in a more direct way, we used event-related transcranial magnetic stimulation (TMS). Here, we investigated the presence and the time course of modulation of motor cortex excitability in young adults who listened to infant cries. Specifically, we recorded motor evoked potentials (MEPs) from the biceps brachii (BB) and interosseus dorsalis primus (ID1) muscles as produced by TMS delivered from 0 to 250 ms from sound onset in six steps of 50 ms in 10 females and 10 males. We observed an excitatory modulation of MEPs at 100 ms from the onset of the infant cry specific to females and to the ID1 muscle. We regard this modulation as a response to natural cry sounds because it was delayed, attenuated to stimuli increasingly different from natural cry, and was absent in a separate group of females who listened to non-cry stimuli physically matched to natural infant cries. Furthermore, the 100-ms latency of this modulation is not compatible with a voluntary reaction to the stimulus but suggests an automatic, bottom-up audiomotor association. The brains of adult females appear to be tuned to respond to infant cries with automatic motor excitation. This effect may reflect the greater and longstanding burden on females in caregiving infants.